Analisis Kebijakan Penyediaan Kapal Tangkap Ikan Bagi Nelayan di Kabupaten Bintan; Studi di Desa Mantang Lama Tahun 2018 - Pangestoeti, Wahjoe; Mahadiansar, Mahadiansar; Aspariyana, Aspariyana (Jurnal Ilmu Administrasi Negara (JUAN), 2019)
Analysis of providing fishing boat policy through Badan Usaha Milik Desa (BUMDes) from village government of Mantang Lama is a strategic step as the effort in preparing economic development and the prosperity of fisherman in coastal area, Bintan Regency, Riau Islands Province. The purpose of this research is to look at the policy formulation that has been done by village government through BUMDes. Then, the researcher wants to study; 1) providing fishing boat policy for fisherman in Mantang Lama, 2) the agreement between village government and the fisherman after the boats operate as the first phase. The research method that is used is qualitative research then will be analyzed descriptively. The result shows that the policy was created solely to develop the fisherman economy, cut off the chain of slavery (fishing boat tauke), and change the fisherman’s mind who usually just rely on people outside of Mantang village. The village government policy of Mantang Lama was created by seeing the great potential of fisherman in Mantang village to be independent and be able in creating a new job demand for the society in their daily life who usually work at land become work at sea in marine and fisheries sector as the housefather of fisherman